2014
DOI: 10.1038/srep05177
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37 Mediates the Antitumor Activity in Hepatocellular Carcinoma: Role for CD57+ NK Cells

Abstract: The biological role of interleukin-37 (IL-37) in cancer is large unknown. Through immunohistochemical detection using 163 primary hepatocellular carcinoma (HCC) clinical specimens, we found the expression of IL-37 was decreased in tumor tissues, and the expression level was negatively correlated with tumor size. High expression of IL-37 in HCC tumor tissues was associated with better overall survival (OS) and disease-free survival (DFS). IL-37 expression in tumor tissues was positively associated with the dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 33 publications
4
103
3
1
Order By: Relevance
“…Previous study also showed that IL‐37 mediated anti‐tumor immune responses through recruiting NK cells to tumor microenvironment in hepatocellular carcinoma 13. However, Ge et al14 found no change in TILs frequencies in tumors over‐expressing IL‐37, suggesting that IL‐37 might not affect the anti‐tumor immune responses in vivo.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous study also showed that IL‐37 mediated anti‐tumor immune responses through recruiting NK cells to tumor microenvironment in hepatocellular carcinoma 13. However, Ge et al14 found no change in TILs frequencies in tumors over‐expressing IL‐37, suggesting that IL‐37 might not affect the anti‐tumor immune responses in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45. Zhang et al15 found that IL‐37 inhibits colon cancer progression via β‐catenin suppression and that a lack of IL‐37 is associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations